2015
DOI: 10.1016/j.jfda.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities and contents of flavonoids and phenolic acids of Talinum triangulare extracts and their immunomodulatory effects

Abstract: In this study, leaves and stems of Talinum triangulare were sequentially extracted with phosphate buffer solution to obtain PTL and PTS (phosphate buffered extracts of T. triangulare leaves and stems), with 75% ethanol to obtained ETL and ETS (ethanol extracts of T. triangulare leaves and stems), or with 90°C boiling water to obtain WTL and WTS (water extracts of T. triangulare leaves and stems). We investigated the antioxidant activities of various T. triangulare extracts, analyzed the extracts' stimulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 27 publications
0
38
0
5
Order By: Relevance
“…The ethanolic extract of Talinum triangulare leaves has been reported to inhibit the production of free radical that often potentiate membrane lipid peroxidation (Adefegha & Oboh, 2011;Liao, Chai, Wang, Chen, & Tsai, 2015). Similar to that, the methanolic extract of Talinum portulacifolium leaves was also reported to inhibit intestinal alpha-glucosidase activity in rats (Thalapaneni et al, 2008) while leave extracts of T. portulacifolium obtained with hexane and water were reported to show antihyperglycemic and antioxidant effects (Babu et al, 2009).…”
mentioning
confidence: 87%
“…The ethanolic extract of Talinum triangulare leaves has been reported to inhibit the production of free radical that often potentiate membrane lipid peroxidation (Adefegha & Oboh, 2011;Liao, Chai, Wang, Chen, & Tsai, 2015). Similar to that, the methanolic extract of Talinum portulacifolium leaves was also reported to inhibit intestinal alpha-glucosidase activity in rats (Thalapaneni et al, 2008) while leave extracts of T. portulacifolium obtained with hexane and water were reported to show antihyperglycemic and antioxidant effects (Babu et al, 2009).…”
mentioning
confidence: 87%
“…This might be due to the presence of phytochemical content and antioxidant potential of the T. occidentalis leaves as reported by Airaodion., et al [9]. Similarly, Swarna and Ravindhran [36] and Liao., et al [37] have reported that T. triangulare leaves are rich in phytochemicals and antioxidants respectively. Furthermore, Airaodion., et al [28] had previously reported that T. triangulare leaves acts as preventive and therapeutic agent against ethanol-induced oxidative stress in Wistar rats due to its antioxidant potential.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be concluded that the increased lipid peroxidation might be one of the factors causing the defect in vascular endothelial growth factor expression and finally producing the impairment in the wound-healing process. These antioxidant activities demonstrated by A. lobata extracts are probably due to flavonoids and phenolics that are common in the species [27,33] and also known to exhibit antioxidant activities [40].…”
Section: Antioxidant Activitiesmentioning
confidence: 99%